Communities and Museums in the 21st Century : Shared Histories and Climate Action. - Brown, Karen. (ICOM Advances in Museum Research Series, 2023)
Communities and Museums in the 21st Century brings together innovative, multidisciplinary perspectives on contemporary museology and participatory museum practice that contribute to wider debates on museum communities, heritage, and sustainability.